MO165: The Controversial Role of Proteinuria and Urinary Output After Radical Nephrectomy in the Development Of Acute Kidney Injury: Double Agents. (3rd May 2022) - Trevisani, Francesco; Cinque, Alessandra; Quattrini, Giulia; Floris, Matteo; Bonzi, Camilla; Rita Rota, Maria; Bettiga, Arianna; Fiorio, Francesco; Capitanio, Umberto; Montorsi, Francesco
Abstract: BACKGROUND AND AIMS: Acute kidney injury (AKI) is increasingly common and associated with adverse short- and long-term outcomes in oncological patients who require radical nephrectomy (RN) for the presence of renal cancer. As defined by the KDIGO Criteria classification system, the diagnosis of AKI is nowadays based on changes in the serum creatinine levels (sCr) or urine output. However, these parameters often underestimate the severity of renal damage and therefore recent insights have resulted in the implementation of proteinuria as means of more accurately assessing for AKI. Proteinuria represents indeed an indicator of both glomerular and renal endothelial injury in chronic disease (CKD), whereas in AKI the presence of proteinuria could be derived from a tubular dysfunction. In the RN scenario, it is still debatable if the development of a mild to severe proteinuria after surgery could be considered a marker of renal damage resulting in AKI or, on the opposite, could be a physiological sign of adaptive compensatory hyperfiltration promoted by the remanent counterlateral kidney.  The aim of our study was to investigate if the development of a postoperative proteinuria plays a positive or negative role in the prevention of AKI in a consecutive cohort of nephrectomized patients affected by renal cancer. METHOD: We enrolled a consecutive cohort of 131 patients who underwent RN due to the presence of a kidney mass suspected of malignancy from 2018 to 2021 in a tertiary care urological Institution. The following data were considered: age, gender, body mass index (BMI), smoke, TNM staging, Fuhrman grading, hypertension, diabetes, cardiovascular events, dyslipidaemia, medical therapy (ACE-inhibitors (ACEi), angiotensin II receptor blockers (ARBs), calcium antagonists, beta blockers and diuretics), proteinuria in 24 h, urine volume in 24 h, preoperative haematocrit and haemoglobin. Serum creatinine (s-Cr) values [Kinetic Picrate standardized (COBAS C 800) for IDMS] were collected before surgery (t 0) and at 24, 48 and 72 h after surgery and at dismissal (respectively t 1, t 2 and tf) to detect renal function fluctuations and the subsequent risk of AKI. GFR was estimated at baseline using CKD-EPI 2012 and MDRD formula. The level of proteinuria was measured at 24 h postoperative and was standardized on the urine volume. Each operated patient underwent the same pre-peri- and postoperative medical protocol in terms of surgical and anesthesiologic management. Patients affected by pre-existing medical nephropathies with proteinuria were excluded. Comparisons between groups were performed using the Kruskal–Wallis rank sum test for numerical variables and Pearson's Chi-squared test for categorical variables. Logistic regression was used to identify variables odds ratio for AKI onset after surgery. RESULTS: Descriptive analysis is shown in Table 1. Our analysis surprisingly underlined that 66% of overall patients experienced AKI after surgery. Moreover, the analysis showed a significant difference ( P value < .05) between the AKI cohort and the non-AKI group concerning basal serum creatinine (sCr), eGFR using both CKD-EPI and MDRD and postoperative urine volume. In particular, the lower the basal sCr or eGFR, the higher was the risk of developing AKI. Concerning the urine output, the median volume of AKI population was significantly less in respect to their counterpart, but far from the critical definition of oliguria or anuria (Table 1 and Figure 1 ). On the contrary, no evidence related to a possible prognostic role of proteinuria was underlined. CONCLUSION: Our work underlined that proteinuria does not represent a valid biomarker for AKI development after RN. On the contrary, basal eGFR, serum creatinine and postoperative urinary volume could be promising tools to predict and follow the acute renal damage after RN.